2009
DOI: 10.1128/cvi.00324-08
|View full text |Cite
|
Sign up to set email alerts
|

Association ofEscherichia coliJ5-Specific Serum Antibody Responses with Clinical Mastitis Outcome for J5 Vaccinate and Control Dairy Cattle

Abstract: Dairy cattle in two commercial Holstein herds were randomly selected to be vaccinated twice with J5, at approximately 60 days and 28 days before the expected calving date, or to be untreated controls. Based on whether milk production changed following clinical mastitis or whether cows were culled or died within 30 days after onset, 51 mastitis cases were classified as severe or mild. J5-specific antibody responses were evaluated by enzyme-linked immunosorbent assay of all 32 severe and 19 mild cases. The amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 17 publications
1
35
1
Order By: Relevance
“…However, despite development of several vaccines in the 1980s, based on the J5 Escherichia coli mutant, such vaccines to date, although demonstrating an ability to reduce the severity of clinical signs and duration of infection, have failed to demonstrate a reduction in the rate of IMI (Hogan et al, 1992;Wilson et al, 2007a). Investigation of the use of J5 coliform vaccines has also demonstrated a positive effect on production in that vaccinated cows have been shown to recover milk yield after a clinical case more quickly than unvaccinated cows (Wilson et al, 2007b(Wilson et al, , 2008(Wilson et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite development of several vaccines in the 1980s, based on the J5 Escherichia coli mutant, such vaccines to date, although demonstrating an ability to reduce the severity of clinical signs and duration of infection, have failed to demonstrate a reduction in the rate of IMI (Hogan et al, 1992;Wilson et al, 2007a). Investigation of the use of J5 coliform vaccines has also demonstrated a positive effect on production in that vaccinated cows have been shown to recover milk yield after a clinical case more quickly than unvaccinated cows (Wilson et al, 2007b(Wilson et al, , 2008(Wilson et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, though a tendency toward a higher milk production in both antimicrobial treatment and E. coli J5 vaccination was observed in the present study, it may not be linked to the effect of contagious pathogens on milk production (no significant difference on milk SCC at 15 days after calving). These findings may be related to the lower clinical mastitis rates observed in this study, and the reduction of the severity of the clinical cases of mastitis and the lower milk losses reported in clinical cases of mastitis in J5-vaccinated cows (Wilson et al 2009). Indeed, Gentilini et al (2012) and Molina et al (2013) also found higher milk production, a reduction in the occurrence of clinical mastitis cases by E. coli in the first 100 days of lactation in J5-vaccinated dairy cows, although no significant difference was found in SCC.…”
Section: Discussionmentioning
confidence: 54%
“…It is known that E. coli J5 bacterin treatment does not prevent IMIs, although the treatment reduces the severity of clinical signs of mastitis (Hogan et al 1992). Indeed, dairy cows that contracted Escherichia coli mastitis and had been vaccinated with E. coli J5 bacterin presented 75% lower milk loss than unvaccinated cows, and the hazard of being culled for all reasons and mastitis were significantly lower for J5 vaccinates (Wilson et al 2009). Altogether, these data can explain, at least in part, the lower amount of milk discarded due to treatment of clinical cases of mastitis and a reduced lactating antimicrobial withdrawal period in animals that received antimicrobial treated and/or E. coli J5-vaccinated dairy heifers found here.…”
Section: Resultsmentioning
confidence: 99%
“…In a recently published study (SCHUKKEN et al, 2014), the efficacy of the novel commercially available (HOGAN et al, 1992;WILSON et al, 2007a). Investigation of the use of J5 coliform vaccines has also demonstrated a positive effect on production in a way that vaccinated cows have been shown to recover milk yield after a clinical case more quickly than unvaccinated cows (WILSON et al, 2007b(WILSON et al, , 2008(WILSON et al, , 2009. The latter research group also provided evidence that increased production of both groups.…”
Section: What Is Vaccine Efficacy?mentioning
confidence: 99%